Kinematiceskie parametry dviženij sportsmenov, napravlennych na sniženie bryzgoobrazovanija pri vypolnenii sportivnych pryžkov v vodu - Raspopova, E. A.; Kurkin, P. E. (Vestnik Moskovskogo gorodskogo pedagogiceskogo universiteta. Serija «Estestvennye nauki», 2017)
The article presents the kinematic water entry parameters, identified for the first time as well as the time and depth of immersion of athletes in the water after performing sports jumps with forward and backward rotation. The actions of athletes in both the surface and underwater parts of the dive have been revealed. The authors came to the conclusion that the actions of the athletes in the underwater part of the jump, aimed at reducing splashing include such braking movements as spreading one`s hands and a somersault. It had been revealed that the performing a somersault should occur after the athlete is completely immersed in the water.